Pre-operative assessment of internal mucosal rectal prolapse in internal hemorrhoids: technical details and results from a single institution - Percalli, Luigi; Passalia, Luigi; Pricolo, Renato; Riccò, Matteo (Acta Biomedica Atenei Parmensis, 2019)
Background: The aim of the study was to assess safety and efficacy of pre-operative assessment for internal mucosal rectal prolapse (IMRP) in internal hemorrhoids, in order to achieve a tailored transanal stapled surgery. Methods: All consecutive patients (January 2011 to December 2014; age 18-80 years), affected by prolapses with II-IV degrees hemorrhoids that underwent Longo procedure with EEA® Auto Suture stapler (Covidien) were included in the present study. Results: A total of 100 consecutive patients (38 females) were enrolled in the study. Preoperative Visual Analogue Scale pain assessment was 7.33±2.68. The mean duration of the procedure was 34.1±17.8 min, and the median hospital stay was 2 days (range 2-6). No major complication occurred, including relapses of mucosal prolapse. Preoperative prolapse measurement with EEA® EEA® Auto Suture stapler (2.3±0.5 cm) was well correlated direct assessment (2.4±0.6, p<0.001), but a proportional bias was identified, with significant preoperative underestimation of IMRP, particularly for lesions larger than 3 cm (around 10% of actual extent). Conclusions: EEA® Auto Suture stapler seems to be safe and effective for a tailored approach to anorectal prolapse due to hemorrhoids. However, it reasonable that its actual impact may have been overestimated, beneficing of the repetitive, direct assessment of the operatory field guaranteed by preoperative IMRP measurement.